Pagbubukas-loob: A proposed filipino theology of evangelical christian spiritual formation - Capaque, George N. (Animo Repository, 2005)
This dissertation attempts to develop a Filipino evangelical theology of spirituality, or more specifically, of evangelical Christian spiritual formation. Christian spiritual formation is broadly understood here as the dynamic process of becoming truly human in Jesus Christ in a particular context. It involves the mutual interaction between human experience (what is culture) and the Judeo-Christian Tradition (what are articulations of life experiences of believers in their faith-relationship with God in Jesus Christ revealed primarily through Scriptures). Spiritual formation is therefore both a cultural (human) process and a faith (and, lived) experience of living the life of wholeness and of intimacy with God. For human formation to take place, there must be an adequate theory of the “person” or “self.” What is the ideal or “enduring self” that formation aims at or aspires to? Both culture and Judeo-Christian Tradition have ideals of what it is to be human. A good ortion of the dissertation therefore deals with both the Filipino way and Tradition’s understanding of being and becoming human. From culture, the theme or concept of pagkataong Pilipino (Filipino person or personhood) is utilized. At the core of pagkatao is loob- the Filipino true self. This true self is experienced as kalooban, katawan and kaluluwa. Loob as kalooban, katawan and kaluluwa is the framework by which we analyze and synthesize the Filipino way of being/becoming. Loob however could only be understood in relation to its context, i.e., Filipino culture, but focusing particularly on Filipino religiosity or folk religion. After the analysis of its context, loob itself is analyzed using phenomenological, linguistic and ethnographic studies.The dissertation next analyzes being /becoming human from the perspective of the Judeo-Christian Tradition. We focus here on the Biblical testimony (itself an evangelical distinctive) of what it means to be fully human. Being human has for its foundation the “image of God.” A biblical-theological synthesis of the image of God is arrived at through the process of grammatico-historical exegeses of relevant texts and comparing them with the history of interpretation in the Tradition. To understand further the notion of “person,” the Christian understanding of God as “person” is also revisited. The concepts of “body,” “spirit,” “soul,” and “heart” are also used in Scripture to represent the self. These are also interpreted to further our understanding of being/becoming human. Being human in the Bible means not only are we created in the image of God but also re-created or renewed in the image of Jesus Christ. We are who we are and who we are becoming to be on the basis of what God through his Holy Spirit has done and continues to do in Jesus Christ. From the side of Christian believers it means faithfully appropriating the means of grace (what are spiritual disciplines) to attain this end. The mutual interaction between the Filipino way of being and doing and the Judeo-Christian understanding of being human yields a contextual theology of Christian spiritual formation. To be authentically human in the Filipino context is to experience being or personhood (pagkatao) in its whole dimensions- lalim (inner self or dimension), lawak (relational being), laman (embodied), and lakas (power, vitality).The process of becoming authentically human (pagpapakatao) is achieved by means of opening oneself (pagbubukas-loob) to one’s true self, to the kapwa, to the world, and ultimately to God. Christian spiritual formation in the Filipino context is pagbubukas-loob. With the reality that we are born and we live in a sinful condition (karupukan ng loob at kapaligiran) pagbubukas-loob happens only when we turn (pagbabalik-loob) to our true self, to our neighbor, and to God. Since it is a process and something that we have yet to attain, it involves a renewal of the whole self (pagbabagong-loob) achieved through the formation of values and virtues consistent with who are in Jesus Christ and the faithful practice of spiritual disciplines appropriate to the Filipino spirit (kalooban).